2019
DOI: 10.1039/c8cp05987j
|View full text |Cite
|
Sign up to set email alerts
|

Effects of interfacial specific cations and water molarities on AOT micelle-to-vesicle transitions by chemical trapping: the specific ion-pair/hydration model

Abstract: Added salts induce micelle-to-vesicle transitions at specific cation concentrations in Hofmeister order by forming polar headgroup–counterion pairs that release water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 67 publications
4
23
0
Order By: Relevance
“…In this sense, the ammonium ion can interact closely with the R‐sulfonate considered chaotropic, according to Collins' concept of matching water affinities (Collins, ; Kunz, ). As a consequence, a chaotropic salt can reduce the effects of head group repulsion, favoring the decrease in interfacial curvature and promoting microemulsion formation (Chen et al, ; Leontidis, ; Liu et al, ; Santos et al, ). This phenomenology is related to the phenomena of “hydration force,” which influences the agglomeration and interfacial activity of surfactant molecules due to the reduction of the hydration repulsion effects (Evans and Ninham, ; Israelachvili and Wennerstrom, ; Kralchevsky et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In this sense, the ammonium ion can interact closely with the R‐sulfonate considered chaotropic, according to Collins' concept of matching water affinities (Collins, ; Kunz, ). As a consequence, a chaotropic salt can reduce the effects of head group repulsion, favoring the decrease in interfacial curvature and promoting microemulsion formation (Chen et al, ; Leontidis, ; Liu et al, ; Santos et al, ). This phenomenology is related to the phenomena of “hydration force,” which influences the agglomeration and interfacial activity of surfactant molecules due to the reduction of the hydration repulsion effects (Evans and Ninham, ; Israelachvili and Wennerstrom, ; Kralchevsky et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the interaction between KCGl headgroup and NH 4 is stronger than other hydrophobic cations. Second, possible hydrogen bonding 49 between NH 4 and amino acid headgroups may also contribute to the packing between amphiphiles with added NH 4 . Thus, the IFT at high surfactant concentration is lower for ammonium ions compared to TMA and TEA .…”
Section: Resultsmentioning
confidence: 99%
“…Water actively influences the hydration and assembling behavior of biological molecules, such as polypeptides, , which is vaguely expressed as hydrophobic effects (HEs). Although the effect of salts on the hydration of biological and synthetic macromolecules, known as the Hofmeister effects, has been extensively studied, the molecular nature of this HE effect and its consequence on the assembling behavior are not clear. It has been reported that the ionic groups pendent to solutes substantially influence the assembling behavior. The long-range effect of water hydrogen bonding structure perturbated by ionic groups is proposed for the discussion in some research studies. However, it is, although controversial, generally considered that the solvation of individual ions does not create a long-range effect for the Hofmeister effects. , This perplexity would be clarified if the ionic-group-dependent hydration could be analyzed on a molecular level.…”
Section: Introductionmentioning
confidence: 99%
“…Self-assembled morphologies of surfactants are found to be dependent on the ionic end group, which is usually rationalized by the variation in the packing parameters caused by the ion pair. 22,23,44 This explanation cannot justify the variable assembling behavior of block copolymers depending on the ionic end groups. 20,21 This perplexity is caused by the negligence of the role of hydration in self-assembly.…”
mentioning
confidence: 99%